Транснаціональна взаємодія університетів в умовах євроатлантичної інтеграції - Авшенюк, Н. М. (НТУ "ХПІ", 2010)
Статья посвящена одной из современных тенденций развития общества знаний – интернационализации высшего образования. Особенное внимание в ней уделено ее основному внешнему проявлению, которым является транснациональное высшее образование. Автор рассматривает основные формы и характеристики исследуемого явления, а именно: мобильность студентов и преподавателей, интернационализацию учебных планов и программ, создание региональных и международных университетских сетей.

The article is devoted to the one of contemporary tendencies of knowledge society development, which is the internationalization of higher education, particularly to its external issues – transnational higher education. The author analyses the main forms and characteristics of the phenomenon under investigation, namely students’ and teachers’ mobility, curriculum internationalization, creation of regional and international universities’ networks etc.
Тransnational universities’ cooperation in the terms of euro-atlantic integration
Keywords: глобалізація; вищі навчальні заклади; реформування вищої школи; міжнародні дослідження; науково-педагогічні центри; працевлаштування